Vozes dos estaleiros: percepção dos carpinteiros navais artesanais de embarcações sobre saúde ocupacional, riscos e prevenção de acidentes em estaleiros da Amazônia costeira (Bragança/PA) - NEGRÃO, Ângelo Solano (Universidade Federal do Pará, 2024)
Introduction: Handcrafted shipbuilding plays a vital role in the production of traditional wooden boats for navigation on the Amazon rivers. However, many ship carpenters face unhealthy conditions and health risks, such as exposure to toxic substances and the impacts of climate change. These challenges can lead to long-term health problems, exacerbated by the lack of adequate protective equipment, affecting not only their ability to work but also their daily activities. Objective: To examine the perception of artisanal boatbuilders, located in the city of Bragança/PA, regarding health, perceived risks in shipyards, and self-protection strategies to prevent accidents. Methods: A qualitative, descriptive, and cross-sectional approach was used. Interviews were conducted with six artisanal ship carpenters, aged between 44 and 67, from different shipyards in Bragança. Participants were selected from previously identified shipyards and recommendations from other professionals, keeping their identities protected through pseudonyms. The interviews, adapted from a previous project, took place in the shipyards during working hours. Data analysis followed Bardin's content analysis methodology, with the organization and coding of responses using NVivo software to identify main themes and subthemes. The study was conducted with proper ethical approval, ensuring the privacy, confidentiality, and consent of participants, respecting all ethical guidelines for research involving humans. Results: Carpenters discussed work-related risks, such as physical accidents when handling heavy materials and the use of toxic chemicals in boat construction. Aware of these risks, they adopted preventive measures, such as using appropriate safety equipment. In terms of self-care, they highlighted the importance of clear communication during high-risk operations, shared responsibility for taking care of less experienced colleagues, and additional precautions due to the remote location of the shipyards. They mentioned a shift to more traditional tools after previous incidents and emphasized collaboration and teamwork to reduce risks in handling heavy materials. Conclusion: Their awareness of work hazards underscores the need for preventive measures and a safety culture, demonstrating a proactive approach to accident prevention. Although the research has limitations, such as geographical restrictions in worker participation, it is the first in the region to address the health of these professionals. Specific occupational health interventions, training to reduce risks, and exploring the relationship between organizational culture and mental health are recommended. Future studies and collaborative strategies are proposed to enhance the health and safety of these workers.